Helicopter engine air intake icing wind tunnel certification test - Lammers, K.; Hoff, S. van 't; Ferschitz, H.; Wannemacher, M. (My University, 2018)
Korea Aerospace Industries LTD (KAI) contracted the Netherlands Aerospace Centre (NLR) to support an Icing Wind Tunnel (IWT) test campaign with the Korean Utility Helicopter KUH-1 engine air intakes aimed at substantiating the compliance with the applicable military regulations for flight in icing conditions. The icing wind tunnel test was performed in the Large Climatic Wind Tunnel (CWT) at Rail Tec Arsenal (RTA) in Vienna, Austria. The test set-up included a full-scale production engine cowling complete with electrothermal anti-icing system and it was installed on a mock-up of the aircraft upper fuselage. The production cowling was used to ensure an exact match and conformity of the thermal properties of the part. To aspirate the engine intakes, NLR designed a dedicated Engine Mass Flow System (EMFS) that simulates the airflow through the engine air and cooling intakes. Two separate industrial radial fans were installed to individually control the mass flow through the engine air intakes and cooling inlets. A continuous mass flow measurement was provided for both channels by anti-iced Pitot-static probes that were calibrated against orifice plate measurements performed prior to the icing test. The tunnel test conditions were scaled for altitude effects by matching key similarity parameters. The test airspeed was based on either Reynolds number scaling or Weber number scaling, depending primarily on the static air temperature. Inter-laminate and surface temperature measurements and observed ice shapes compared favourably with artificial and natural icing flight test results obtained with the same intake configuration. The IWT testing supplemented the flight test results by providing more stable icing conditions with control over drop size, and covering the corner points of the icing envelope.